The Importance of Biobelts from the Point of View of the Biodiversity of Epigeic Groups - Jana Ivanič Porhajašová; Mária Babošová; Peter Schultz; Miroslava Kačániová (Scientific Papers Animal Science and Biotechnologies)
The importance of biobelts lies mainly in the natural greening of the ecosystem. The loss of biodiversity is currently one of the biggest problems and the final challenge we face. The agricultural landscape is becoming increasingly less suitable habitat for many species of plants and animals. The answer to the decreasing biodiversity in the agricultural landscape is various measures that support biodiversity. The aim of the work was to evaluate the abundance, structure and dominance of the occurrence of epigeic groups present in biobelts in the southwestern part of Slovakia. Biobelts perform many primarily positive functions within agroecosystems. The ground trap method was used to determine the presence of epigeic groups. 19 taxonomic groups were obtained, with a dominant representation of Coleoptera, Collembola, Acarina, Formicoidae, Opilionida Araneida. From the point of view of biodiversity, minorly represented groups such as Heteroptera, Diplopoda, Chilopoda, Dermaptera, Lumbricidae, etc. are also important. The calculated diversity index reached a value of 2.243 in the 1st year and 1.778 in the 2nd year. The faunal similarity of the variants reached a value of 94.44%. Despite the fact that these are ecological areas intended for target groups of animals, in the case of all types of biobelts, these are areas from which the entire biosystem benefits.